Culture: The missing link in health research. (December 2016) - ,; Baquet, Claudia R.; Bell, Ronny A.; Burhansstipanov, Linda; Burke, Nancy J.; Dibble, Suzanne; Elwood, William; Garro, Linda; Gravlee, Clarence C.; Guarnaccia, Peter; Hecht, Michael L.; Henderson, Jeffrey; et al.
Abstract: Culture is essential for humans to exist. Yet surprisingly little attention has been paid to identifying how culture works or developing standards to guide the application of this concept in health research. This paper describes a multidisciplinary effort to find consensus on essential elements of a definition of culture to guide researchers in studying how cultural processes influence health and health behaviors. We first highlight the lack of progress made in the health sciences to explain differences between population groups, and then identify 10 key barriers in research impeding progress in more effectively and rapidly realizing equity in health outcomes. Second, we highlight the primarily mono-cultural lens through which health behavior is currently conceptualized, third, we present a consensus definition of culture as an integrating framework, and last, we provide guidelines to more effectively operationalize the concept of culture for health research. We hope this effort will be useful to researchers, reviewers, and funders alike. Highlights: The first multidisciplinary consensus definition of culture for health is presented. Recognition that both what culture is and what culture does is required to operationalize the concept in research. The dynamic nature of culture creates subcultural differences over time and space. The culture framework enhances the explanatory power of culture on health behavior. Culture is a framework for the social determinants of health.